Low genetic variation between isolates of Citrus leaf blotch virus from different host species and of different geographical origins - Vives, María C.; Rubio, Luis; Galipienso, Luis; Navarro, Luis; Moreno, Pedro; Guerri, José (2017)
The population structure and genetic diversity of Citrus leaf blotch virus (CLBV) were estimated by single-strand conformation polymorphism and nucleotide sequence analyses of two genomic regions located within the replicase (R) and the coat protein (C) genes. Analysis of 30 cDNA clones of each genomic region from two CLBV isolates showed that both isolates contained a predominant haplotype and others closely related. Analysis of 37 CLBV Spanish field isolates showed low genetic diversity (0.0041 and 0.0018 for genomic regions R and C, respectively). Comparison of 14 CLBV isolates from Spain, Japan, USA, France and Australia showed genetic diversities of 0.0318 (R) and 0.0209 (C), respectively. No correlation was found between genetic distance and geographical origin or host species of the isolates. The ratio between nonsynonymous and synonymous substitutions was the lowest found in a plant virus, indicating a strong negative selective pressure in both genomic regions.